Transient global amnesia: clinical features and prognostic factors suggesting recurrence - Alessandro, Lucas; Calandri, Ismael L.; Suarez, Marcos Fernández; Heredia, María L.; Chaves, Hernán; Allegri, Ricardo F.; Farez, Mauricio F. (Arquivos de Neuro-Psiquiatria, 2019)
The risk of recurrence of new amnesia events in patients having previously experienced transient global amnesia (TGA) ranges between 2.9-23.8%.Objective: Our objective was to search for recurrence predictors in TGA patients.Methods: Retrospective analysis to identify recurrence predictors in a cohort of 203 TGA patients from a single center in Buenos Aires, Argentina, diagnosed between January 2011 and March 2017 Clinical features and complementary studies (laboratory results, jugular vein Doppler ultrasound and brain MRI) were analyzed. Comparison between patients with recurrent versus single episode TGA was performed, applying a multivariate logistic regression model.Results: Mean age at presentation was 65 years (20-84); 52% were female. Median time elapsed between symptom onset and ER visit was two hours, with the average episode duration lasting four hours. Mean follow-up was 22 months. Sixty-six percent of patients referred to an identifiable trigger. Jugular reflux was present in 66% of patients; and 22% showed images with hippocampus restriction on diffusion-weighted MRI. Eight percent of patients had TGA recurrence. Patients with recurrent TGA had a more frequent history of migraine than patients without recurrence (37.5% vs. 14%; p = 0.03). None of the other clinical characteristics and complementary studies were predictors of increased risk of recurrence.Conclusions: Patients with migraine may have a higher risk of recurrent TGA. None of the other clinical characteristics evaluated allowed us to predict an increased risk of recurrence. Although the complementary studies allowed us to guide the diagnosis, they did not appear to have a significant impact on the prediction of recurrence risk.
Keywords: Amnesia, anterograde; recurrence; amnesia, transient global